Y-STR Haplotype Diversity among the Population of District Haridwar, Uttarakhand, India (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
Seventeen Y-chromosomal short tandem repeat (Y-STR) loci in a population sample of Dist. Haridwar, Uttarakhand, India was analysed to find out the haplotype diversity (HD). Blood samples were collected from 85 unrelated male individuals and genomic DNA isolation was carried out by the standard organic extraction method, followed by multiplex PCR amplification using AmpFl STR Y-filer polymerase chain reaction (PCR) amplification kit and subsequent genotyping. A total of 75 haplotypes were observed among the studied samples, out of which 69 were unique. Allele frequency and gene diversity were calculated. HD and discrimination capacity were found to be 0.991 and 0.8823, respectively. Haplotypes of Dist. Haridwar, Uttarakhand population was compared with that of other Indian populations using analysis of molecular variance tool to measure the genetic relatedness between various populations of India.
Keywords: Discrimination capacity; Genotyping; Haplotype diversity; PCR; Polymorphism; Uttarakhand; Y-STR